2020
DOI: 10.20944/preprints202012.0778.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chikungunya Manifestations and Viremia in Patients Who Presented to the Fever Clinic at Bangkok Hospital for Tropical Diseases During the 2019 Outbreak in Thailand

Abstract: Chikungunya virus is an Alphavirus belonging to the family Togaviridae that is transmitted to humans by an infected Aedes mosquito. Patients develop fever, inflammatory arthritis, and rash during the acute stage of infection. Although the illness is self-limiting, atypical and severe cases are not uncommon, and 60% may develop chronic symptoms that persist for months or even for longer durations. Having a distinct periodical epidemiologic outbreak pattern, chikungunya virus reappeared in Thailand in December 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
(92 reference statements)
1
1
0
Order By: Relevance
“…We previously demonstrated that arthralgia and a decrease in lymphocyte count are associated with higher viremia. 49 In the present study, we also observed a lower number of circulating lymphocytes in patients with arthritis, along with a lower cycle threshold value and other signs of systemic involvement and inflammation. The elevated serum creatinine levels in adults could have been due to worsening kidney function associated with pre-existing comorbidities.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We previously demonstrated that arthralgia and a decrease in lymphocyte count are associated with higher viremia. 49 In the present study, we also observed a lower number of circulating lymphocytes in patients with arthritis, along with a lower cycle threshold value and other signs of systemic involvement and inflammation. The elevated serum creatinine levels in adults could have been due to worsening kidney function associated with pre-existing comorbidities.…”
Section: Discussionsupporting
confidence: 78%
“…50 We took this opportunity to compare the clinical and laboratory profiles of patients in the present and previous CHIKV infection studies with our dengue patient cohort. 34,49 Early in the onset of illness, dengue cases exhibited an increased frequency of headaches compared with both CHIKV patient cohorts. Decreases in the number of circulating leukocytes, neutrophils, lymphocytes, and platelets were more common in dengue cases than in CHIKV infection cases in the present study.…”
Section: Discussionmentioning
confidence: 99%